IMPLEMENTASI MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI BAHASA INGGRIS PADA SISWA KELAS VIII DI SMP ANTONIUS NABIRE - Whisnubrata, Antonius Awan Asta Adhiprana; Dimara, Johanes; Nabila, Almaz Rizkika; Saboan, Stefani (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2024)
This study aims to investigate the implementation of the Project-Based Learning model to improve English communication skills among seventh-grade students at SMP Antonius Nabire. This research employed the Pre-Experimental Design method, with a sample of 29 eighth-grade students. Data were collected using an oral test (speaking test). The results of the study showed that the application of the Project-Based Learning (PjBL) model significantly improved students' communication skills in the English subject. Before the implementation of PjBL, the majority of students fell into the failing category with an average score of 57.58%. However, after the implementation of PjBL, there was a significant improvement, with the average student score reaching 94.48%, and the majority of students achieving the "very good" qualification. These results align with various studies that assert PjBL's effectiveness in enhancing communication skills, as students actively engage in discussions, collaboration, and project presentations. In addition to improving academic abilities, PjBL also hones essential social skills needed for 21st-century learning. The N-Gain results showed that all students achieved a high qualification in communication skills, confirming that PjBL is an effective method for significantly increasing student engagement and communication skills.